Pengembangan Panda Gigi Sebagai Media Guru dalam Pembelajaran Menggosok Gigi Disabilitas Intelektual Ringan - Nanda Amanda; Setia Budi; Elsa Efrina; Yosa Yulia Nasri (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study was conducted to address the limited availability of learning media for teaching toothbrushing skills to children with mild intellectual disabilities in Special Schools (SLB). Teachers generally rely on lectures and direct demonstrations, making it difficult for students to understand the correct sequence of toothbrushing independently. Therefore, a structured and visually engaging learning medium is needed. This study aimed to develop Panda Gigi (Guide to Brushing and Caring for Teeth) as a learning medium for teachers and to evaluate its validity and practicality. The research employed the Research and Development (R&D) method using the 4D model: Define, Design, Develop, and Disseminate. Validation was conducted by material and media experts, while practicality was assessed through teacher responses at SLB Bakti Padang. The results showed validity scores of 69.09% from the material expert and 86.15% from the media expert. The practicality test yielded a score of 87.69%. These findings indicate that Panda Gigi is a valid and practical medium for teaching toothbrushing skills to children with mild intellectual disabilities